Multicolor far-field fluorescence nanoscopy through isolated detection of distinct molecular species. - Bossi, M; Fölling, J; Belov, V; Boyarskiy, V; Medda, R; Egner, A; Eggeling, C; Schönle, A; Hell, S (2008)
By combining the photoswitching and localization of individual fluorophores with spectroscopy on the single molecule level, we demonstrate simultaneous multicolor imaging with low crosstalk and down to 15 nm spatial resolution using only two detection color channels. The applicability of the method to biological specimens is demonstrated on mammalian cells. The combination of far-field fluorescence nanoscopy with the recording of a single switchable molecular species at a time opens up a new class of functional imaging techniques.